MALAYSIA STROKE CONFERENCE 2022 3: E-Poster Presentation - 2022, Malaysia Stroke Conference (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
1. STROKE IN SEVERE COVID-19 INFECTION: A CROSS-SECTIONAL STUDY 2. THE PECULIAR STROKE SYNDROMES 3. FIBROMUSCULAR DYSPLASIA IN A YOUNG STROKE 4. EXTENSIVE CORPUS CALLOSUM INFARCT AS AN UNUSUAL PRESENTATION IN TOTAL ANTERIOR CIRCULATION INFARCT STROKE: A CASE REPORT 5. THROMBOTIC THROMBOCYTOPENIA PURPURA CAUSING CONCURRENT CEREBRAL ISCHEMIA AND INTRACRANIAL BLEED: A CASE REPORT 6. STROKE CODE ACTIVATIONS IN HOSPITAL SEBERANG JAYA 3 YEARS EXPERIENCE 7. IMPACT OF ATRIAL FIBRILLATION IN FUNCTIONAL OUTCOME FOR ACUTE STROKE 8. CHALLENGES AND OUTCOMES IN INTRAVENOUS THROMBOLYSIS IN POSTERIOR CIRCULATION INFART (POCI) IN HOSPITAL SULTANAH NUR ZAHIRAH: A RETROSPECTIVE STUDY 9. BETTER LATE THAN NEVER 10. THE DEMOGRAPHICS, DISEASE PATTERN, INTERVENTION AND OUTCOMES OF STROKE PATIENTS PRESENTING TO EMERGENCY DEPARTMENT AT INSTITUT JANTUNG NEGARA IN 2019 (Non-clinical study)